Data linkage to evaluate the long-term risk of HIV infection in individuals seeking post-exposure prophylaxis - Frédérique Hovaguimian (Nature Portfolio, 2021)
Individuals seeking post-exposure prophylaxis (PEP) for HIV may represent an important risk group for future HIV infection. Here the authors find HIV infections at long-term follow-up in 22 of 348 men who have sex with men, and 0 of 623 other PEP seekers.